Dental microwear and mesowear raw data for Equus ferus and Rangifer tarandus from Sesselfelsgrotte - Florent Rivals (Zenodo, 2021)
Quantitative data for the dental microwear and mesowear analyses on Equus ferus and Rangifer tarandus from the Middle Palaeolithic sequence of Sesselfelsgrotte(Bavaria, Germany)